Effects of uni and bilateral castration on growth performance and lipid metabolism in yellow cattle. Issue 1 (1st February 2023) - Shah, Ali Mujtaba; Wang, Zhisheng; Ma, Jian; Hu, Rui; Li, Xiang; Li, Guangyang; Yao, Xiaohe; Guo, Yixin; Peng, Quanhui; Xue, Bai; Wang, Lizhi
Abstract: This study was conducted to examine the influence of uni and bilateral castration on growth performance and lipid metabolism in yellow cattle. Eighteen 9-month-old healthy yellow cattle (average body weight 184.03 ± 4.09 kg) were selected and divided into three groups: The uncastrated cattle (C), half castrated cattle (HC) and full castrated cattle (FC). The results showed that the growth rate of FC group was significantly reduced as compared to HC and C group, while the feed to gain ratio exhibited an opposite trend. The concentrations of triglycerides (TG), low-density lipoprotein cholesterol (LDL) and high-density lipoprotein (HDL) were increased significantly in FC group from day 60 to the end of the trial compared to HC and control groups. Serum testosterone concentration of FC group cattle was decreased from day 60 to 120 d of the trial compared to HC and control groups. The concentration of the lauric acid in FC cattle was significantly increased from the HC and control groups. In the FC group, the acetyl-CoA carboxylase alpha (ACACA), ACC and fatty acid synthase (FAS) gene expression levels were significantly higher compared to control and HC groups. Our results of this study suggest that bilateral castration increased the lipid metabolism and fatty acid composition compared to unilateral castrated and un-castrated cattle. Highlights: Bilateral castration alters the growth performance in yellow cattle. Bilateral castration alters hormones levels and lipid metabolites levels in serum. Bilateral castration improves the lipid metabolism and fatty acid profile.